MORFOFONEMIK BAHASA PAMONA DIALEK BARE’E - NFN Aminah (Balai Bahasa Sulawesi Tengah, 2014)
The aim of this research is describing the morfofonetic process in Pamona language on Bare”e Benteng dialect. Descriptive qualitative method was applied by using write and recorded technique. Document analysis also applied based on previous reserach of Bare’e Benteng dialect. The data was analyzed based on structural linguistic. The result of the research showed that there was assimilation process in Langugae Pamona in Bare’e dialect in the form of the change of sound.